Upaya Peningkatan Pengetahuan tentang Penanganan Cidera Olahraga pada Pemain Sepak Bola di Komunitas Jambi Fun Soccer - Putra Hadi; Indah Permata Sari (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Football is a game of playing the ball using the feet, with the intention of scoring as many goals as possible based on the rules that have been set. So that in order to do all of that well, athletes must be in prime physical condition without any physical disturbances. Football is also a sport where body contact often occurs, in the implementation of sports there are still many people who have not carried out sports activities properly, resulting in injuries. Injuries in football games sound familiar and seem inseparable, but through community service entitled Efforts to Increase Knowledge About Handling Sports Injuries in Football Players in the Jambi Fun Soccer Community, it is hoped that it can provide an understanding to football players about the factors that cause injuries in soccer game. Community service activities will be carried out in December 2022 using the discussion method and presenting materials and leaflets and demonstrating first aid in sports injuries. This community service aims to increase knowledge about handling sports injuries to soccer players in the Jambi Fun Soccer community. The positive responses given by the players were very diverse and on average they gave very satisfied responses to the implementation of this work program